The Influence of Corporate Social Responsibility and IntellectualCapital Disclosure on Financial Performance of Financial Industry Companies In Malaysia And Indonesia - Sindy Ponto; Eko Budi Santoso (Accounting Study Program, Universitas Ciputra Surabaya, 2020)
Abstract: The purpose of this research is to analyze the influence of Corporate Social Responsibility and Intellectual Capital on the financial performance of financial industry companies in Malaysia and Indonesia. The independent variable in this research was VAIC developed by Pulic which is used as a measurement of Intellectual Capital and checklist Corporate Social Responsibility to measure Corporate Social Responsibility, while the dependent variable of this research was financial performance which is proxied by Return on Assets, Return on Equity and Capital Adequacy Ratio. The samples of this study were financial industry companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange with the research period of 2013-2018. Data collection used in this study was purposive sampling technique. The results indicated that (1) Corporate Social Responsibility has positive influence to the financial performance (ROA and ROE) but has negative influence to the financial performance (CAR), (2) Intellectual Capital has positive influence to the financial performance (ROA and ROE) but has negative influence to the financial performance (CAR), (3) Corporate Social Responsibility and Intellectual Capital has positive influence to the financial performance (ROA, ROE and CAR). Keywords: Corporate Social Responsibility; Intellectual Capital; financial performance; Value Added Intellectual Coefficients (VAIC).